Prevalence of mental distress and associated factors among caregivers of patients with severe mental illness in the outpatient unit of Amanuel Hospital, Addis Ababa, Ethiopia, 2013: Cross-sectional study. Issue 1 (December 2015) - Sintayehu, Mezinew; Mulat, Haregwoin; Yohannis, Zegeye; Adera, Tewodros; Fekade, Maereg
Abstracts Background Caregivers like family members or other relatives are central and provide not only practical help and personal care but also give emotional support, and they are suffering from plenty of challengeable tasks. These, eventually, cast out family caregivers into multidimensional problems prominently for mental distress like depression, anxiety, sleep problem and somatic disorder which are followed by physiologic changes and impaired health habits that ultimately lead to illness and possibly to death. Numerous studies demonstrate that mental distress of caregivers are two times compared to general populations. Despite it was not uncommon to observe manifestations of caregivers' mental distress, yet there was no study on this area. Therefore, this study was intended to assess the prevalence of mental distress and associated factors among the caregivers of persons with severe mental illness in the out patients unit of Amanuel Hospital, Ethiopia. Methods Institutional based cross sectional study was conducted from May 1 to 31, 2013 at Amanuel Hospital, Addis Ababa, Ethiopia. Systematic random sampling technique with "k" interval of 13 was employed to withdraw a total of 423 participants from study population. Five psychiatric nurses carried out interview by using standardized and validated Self Reported Questionnaire (SRQ 20). Descriptive statistics, binary and multivariate logistic regression analysis were conducted. Results This study revealed that the overall prevalence of mental distress was found to be 221(56.7 %). The factors like missed social support, two or more times admission of patient, care giving for psychotic patient, being farmer and being female were found to be predictors for mental distress of caregivers with this [AOR 95 % CI = 9.523(5.002, 18.132)], 3.293(1.474, 3.3560), 2.007(1.109, 3.634), 2.245(1.129, 4.463) and 3.170(1.843, 5.454)] respectively. Conclusions In this respect the study observed that there was a higher level of mental distress experienced by caregivers of patients with severe mental illness in Amanuel Hospital, and social support are strongly associated with mental distress besides to other variables. Effectively planned interventions have to be targeted at alleviating mental distress and actions like on-going psycho-education and mutual support that could expand social support should be implemented in Amanuel hospital health service delivery system.